Assessing Long‐Term Neurologic Outcomes in SAMD9L‐Related Ataxia‐Pancytopenia Syndrome - Zingariello, Carla D.; Chen, Dong‐Hui; Raskind, Wendy H.; Slayton, William B.; Subramony, Sub; Severance, Joyce; Feagle, Megan; Rasmussen, Sonja A. (Movement disorders clinical practice (Hoboken, N.J.), 2024)
Background Most published reports on SAMD9L‐related ataxia‐pancytopenia syndrome (ATXPC) have emphasized the hematologic findings. Fewer details are known about the progression of neurologic manifestations and methods for monitoring them. Cases We present six individuals from two families transmitting a heterozygous variant in SAMD9L, exhibiting clinical variations in their hematologic and neurologic findings. Serial motor function testing was used to monitor motor proficiency over a 2 to 3 year period in the proband and his father from Family 1. Conclusions Our case series focuses on the neurologic progression in patients with heterozygous variants in SAMD9L. Patients with ATXPC should be followed to evaluate a wide range of neurologic manifestations. Serial motor function testing using a standardized method is helpful to track changes in balance and coordination in children and adults with ATXPC and could aid in a future extended natural history study.